A New 4-D Hyperchaotic Liu System with a Curve Equilibrium, Its Bifurcation Analysis and Circuit Simulation - Vaidyanathan, Sundarapandian; Hannachi, Fareh; Balthazar, José Manoel [UNESP]; Mohamed, Mohamad Afendee; Sambas, Aceng (Springer Nature, 2025)
In this research work, we construct a new 4-D hyperchaotic Liu system with a curve equilibrium. Our construction is achieved by introducing a feedback control to the 3-D Liu chaotic system (2004). We describe our new results with a dynamic analysis using bifurcation diagrams and Lyapunov exponents. Since it is shown that the new hyperchaotic Liu system exhibits a curve equilibrium, the system has hidden hyperchaotic attractors. We show that the new hyperchaotic Liu system exhibits multistability and coexisting attractors. Using NI MultiSim 14.2 software, we design an electronic circuit for the proposed hyperchaotic Liu system with a curve equilibrium, which will be useful for practical implementations of the proposed hyperchaotic system.